(Table 1) Geochemistry of carbonate veins from basalts of the eastern flank of the Juan de Fuca Ridge, ODP Leg 168 - Rosalind M Coggon; Damon A H Teagle; Matthew J Cooper; David A Vanko (PANGAEA, 2004)
Leg 168 of the Ocean Drilling Program (ODP) investigated the heat flow, fluid chemistry and crustal alteration associated with ridge flank hydrothermal systems. Ten sites were drilled on the eastern flank of the Juan de Fuca Ridge, along an 80 km transect, between 20 and 100 km east of the spreading centre. Recovered cores consisted of 100-500 m of sediment with shallow penetration (1.7-48.1 m) into the underlying igneous basement (0.8-3.6Ma). Here we use the composition of calcium carbonate minerals, from veins within the upper basement, to reconstruct the evolving chemistry of hydrothermal fluids with increasing crustal age and sediment cover thickness. We show for the first time a clear link between the alteration of the basement rocks as recorded by secondary minerals, and the nearbasement sedimentary pore fluids, which are often assumed to be representative of the basement fluids responsible for low temperature alteration of the upper crust. Carbonates precipitated from basement fluids that ranged in strontium isotopic composition from near-modern seawater (87Sr/86Sr =~ 0.70918) to the near-basement pore fluid values at any one site. 87Sr/86Sr ratios are independent of mineralogy with both aragonite and calcite precipitating from variably evolved fluids with the range in carbonate 87Sr/86Sr increasing with crustal age. A parallel geochemical evolution of basement fluids and sediment porewaters is shown since 87Sr/86Sr ratios of near-basement pore fluids decrease from 0.709013 to 0.707108 away from the ridge axis. A correlation exists between 87Sr/86Sr ratios and d18O-calculated fluid temperatures, with more geochemically evolved carbonates having precipitated from warmer fluids. Basement fluid compositions, calculated from carbonate Sr, Mg, Fe and Mn concentrations combined with suitable partition coefficients, are also temperature-dependent. Given an observed increase in basement temperature with age, from 16°C to 64°C along the transect, a progressive chemical development of basement fluid is demonstrated. Carbonate veins in volcanic basement from ODP Holes 504B and 896A, on the Costa Rica Rift, record the same temperature compositional evolution of basement fluid as those from the Juan de Fuca Ridge flank. Although these locations have different thermal histories and therefore must have experienced different temporal geochemical evolution of basement fluid, basement temperature appears to be the dominant control on basement fluid composition.
Supplement to: Coggon, RM et al. (2004): Linking basement carbonate vein compositions to porewater geochemistry across the eastern flank of the Juan de Fuca Ridge, ODP Leg 168. Earth and Planetary Science Letters, 219(1-2), 111-128, https://doi.org/10.1016/S0012-821X(03)00697-6